2021
DOI: 10.3389/fnins.2021.651710
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Topological Network in Parkinson’s Disease With Impulse Control Disorders: A Resting-State Functional Magnetic Resonance Imaging Study

Abstract: In recent years, neuroimaging evidence shows that the brains of Parkinson disease (PD) with impulse control disorders (ICDs) patients have functional disconnection changes. However, so far, it is still unclear whether the topological organization is damaged in PD patients with ICD. In this study, we aimed to explore the functional brain network in 18 patients with PD with ICDs (PD-ICD) and 18 patients with PD without ICDs (PD-nICD) by using functional magnetic resonance imaging and graph theory approach. We fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Therefore, based on our current and previous findings, it appears that efficient communication throughout all brain regions (an optimal balance between network segregation and integration) is important in controlling impulsiveness, particularly impulsive choice. Indeed, previous studies in clinical patients who lacked impulsive control showed abnormal small-worldness in functional and structural brain networks 72 75 .…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, based on our current and previous findings, it appears that efficient communication throughout all brain regions (an optimal balance between network segregation and integration) is important in controlling impulsiveness, particularly impulsive choice. Indeed, previous studies in clinical patients who lacked impulsive control showed abnormal small-worldness in functional and structural brain networks 72 75 .…”
Section: Discussionmentioning
confidence: 98%